Research on the Evolution and Transformation of Administrative Discretion Regulation: A Systematic Review of Literature - ChunMei, Liang; Kadir, Nadhrah A; WenRui, Zhang (Theoretical and Practical Research in Economic Fields; Vol 17 No 1 (2026): TPREF Volume XVII Issue 1(37) March 2026, 2026)
This study discusses the development history, recent research, and future directions of regulating the exercise of administrative discretion. Through a systematic literature review, we identified 47 papers published between 1983 and 2025. These studies primarily analyzed the evolution of administrative discretion, the relationship between administrative discretion and the administrative environment, and regulatory approaches for subjects at different levels of administrative discretion. Based on the analysis, we identify a future normative logic for regulating the exercise of administrative discretion that will emphasize a legal focus supplemented by rationality. Administrative discretion is increasingly integrated with ICT, leading to a separation between its consideration and implementation, necessitating a corresponding distinction in its regulation. This study further summarizes current research challenges, including instrumental fragmentation, a lack of evaluation, and insufficient adaptability. We recommend strengthening theoretical integration, empirical research, and localization to promote the systematic development of administrative discretion regulation. This study is the first to systematically integrate multi-dimensional normative research findings at the micro, meso, and macro levels, constructing an interdisciplinary holistic analytical framework for the normative exercise of administrative discretion. By revealing the intrinsic connections and evolution of normative logic at different levels, this study not only enriches the theoretical foundation for the rational exercise of administrative discretion but also provides new explanatory paths and operational insights for institutional design and practical improvement of discretion in the context of digital transformation.